2011
DOI: 10.2169/internalmedicine.50.3713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clopidogrel Resistance in Ischemic Stroke Patients

Abstract: Objective Clopidogrel has potent antiplatelet effects, but recent interest has focused on clopidogrel resistance, in which platelet function is not inhibited despite taking the drug. This study evaluated clopidogrel resistance in ischemic stroke patients. Methods After taking oral clopidogrel 75 mg/day for "1 week, platelet aggregometry was performed by turbidimetry in all patients, and by a screen filtration pressure method using whole blood in 37 patients. Using turbidimetry, resistance was defined as platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…Lee et al reported that the rate of clopidogrel resistance defined as a % inhibition <40% was 42.9% (13). The rate of clopidogrel resistance using 20 μM ADP and <20% inhibition was 29% in the present study, which was higher than our previous findings (8-18%) using turbidimetry, 1-4 μM ADP and screen filtration pressure (7). The frequency of clopidogrel resistance was dependent upon the cut-off point or type of measurement method used.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Lee et al reported that the rate of clopidogrel resistance defined as a % inhibition <40% was 42.9% (13). The rate of clopidogrel resistance using 20 μM ADP and <20% inhibition was 29% in the present study, which was higher than our previous findings (8-18%) using turbidimetry, 1-4 μM ADP and screen filtration pressure (7). The frequency of clopidogrel resistance was dependent upon the cut-off point or type of measurement method used.…”
Section: Discussioncontrasting
confidence: 80%
“…Recently, much attention has been paid to clopidogrel resistance (1-6), however, there are few reports of clopidogrel resistance in ischemic stroke patients. Using a turbidimetric method with a low dose of ADP (1-4 μM) and screen filtration pressure, we determined that the rate of clopidogrel resistance in patients with ischemic stroke is 8-18% (7).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively limited, available literature indicates that the prevalence of HTPR in CVD varies between 3-62% with aspirin monotherapy [40,65], 8-61% with clopidogrel monotherapy [46,49,77] and 56-59% when dipyridamole is added to aspirin [27] in the early, subacute or late phases after TIA/stroke onset. These summary figures for clopidogrel-HTPR exclude data from two studies that confirmed that the standard C-ADP cartridge on the PFA-100 is not sensitive at detecting the antiplatelet effects of clopidogrel if one uses a cross-sectional, case-control definition of HTPR [28,37].…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo HTPR was evaluated with optical aggregometry in PRP in 72 patients within 7-62 days of non-cardioembolic TIA/ ischaemic stroke who were on 75 mg of clopidogrel daily for !1 week [49]. Clopidogrel-HTPR was seen in 8.3% with 1 mmol/L ADP and 18.1% with 4 mmol/L ADP.…”
Section: Platelet Aggregometrymentioning
confidence: 91%
“…In Japan, the administration of aspirin, clopidogrel and/or cilostazol is recommended to prevent the recurrence of noncardiogenic ischemic stroke. We previously measured the degree of platelet aggregation in noncardiogenic ischemic stroke patients and reported that 8-29% of the patients had clopidogrel resistance (7)(8)(9). Several factors, including genetic polymorphisms of the drug-metabolizing enzyme CYP2C19, have been identified as causes of clopidogrel resistance (10,11).…”
Section: Introductionmentioning
confidence: 99%